The effect of wire rupture on flexural behavior of 45-year-old post-tensioned concrete bridge girders. (15th October 2021) - Jeon, Chi-Ho; Sim, Chhengty; Shim, Chang-Su
Highlights: Two PSC girders recovered from a 45-year-old bridge are inspected and tested in this paper. Actual material properties are evaluated from cylinder tests of concrete cores and tensile test of steel wires. Residual prestressing force is evaluated by cutting of a few wires. The flexural capacity of the girder with damaged steel wires is evaluated using the material properties and strain-compatibility method. Abstract: Current maintenance practices for aging prestressed concrete bridges are facing challenging tasks to judge structural adequacy and remaining service life even with insufficient information and invisible deterioration. For prestressed concrete bridges, remaining prestress forces and corrosion of strands are the most crucial data. To accumulate the data, full-sized and deteriorated 45-year-old prestressed concrete bridge girders were recovered from an existing bridge. The post-tensioned girders were tested to observe key performance indicators such as cracking, yielding and crushing. The proposed strain compatibility method considering average tested material properties and measured prestressing force provides reasonable estimation of the flexural capacity of the old prestressed concrete girders. From the observed flexural behavior, a flexural cracking can give a good indication of the residual prestressing force. Based on the experiment, discussion on the assessment of existing bridges and shift from safety-oriented limit states to quantitative approach for extended service life.